Penyelesaian Wanprestasi DalamPerjanjian Kredit Dengan Jaminan Hak Tanggungan(Studi Kasus Di Pt. Bank Danamon Tbk. Dsp Cabang Tanjungpandan) - Pratiwi, Sherly; , Septarina Budiwati, S.H., M.H; , Darsono, S.H., M.Hum (2016)
The purpose of this study is to describe the process of tort settlement with warranty deed and explain the constraintssuffered by Bank Danamon Tbk. DSP Company Branch Tanjungpandan in the settlement processes with warranty deed and the way to resolve it.The research method uses empiric juridical approach, data sources consist of interview as primary data whereas statutes and scientific books as the secondary data.The data analysis method is qualitativedescriptive. The results showed that the settlement processes with warranty deed by exercising preventive and repressive measures, a warning letter and the letter of summons as measurements. Juridical and non juridical are the constraintssuffered by Bank Danamon Tbk. DSP Company Branch Tanjungpandan, the settlement is by exercising periodic examination of the files and documents of the debtor.